Condução de estudos de eliciação vegetal: como estimar o real poder eliciador de uma molécula? - Ducatti, Rafael Dal Bosco (2024)
Wheat constantly suffers from the attack of diseases that, in addition to reducing the crop's quantitative yields, also affect kernels' final quality. An example is the disease called Gibberella. Caused by the phytopathogenic fungus Fusarium graminearum (sexual phase: Gibberella zeae), this disease causes yield reductions of between 18.6% and 39.9% in Brazilian fields and can cause quality losses of up to 100% due to the synthesis and accumulation of the trichothecene deoxynivalenol (DON) by F. graminearum. To worsen this scenario, it is believed that the synthesis of these mycotoxins occurs as a defense mechanism of Fusarium against biotic and/or abiotic stressor agents, including the use of inefficient fungicides. In the search for a more sustainable agriculture and to find complementary products that help to increase the efficiency of agricultural defensives, biostimulants based on seaweed, fit in. Carrageenan, a sulfated polyanionic polysaccharide exclusive to red algae (Rhodophyta) proves to be an excellent plant elicitor as it has different degrees of sulphation, giving the product a long-lasting effect on the plant elicitation process. However, testing plant elicitors is not a trivial process. These experiments demand good planning and in-depth knowledge of plant physiology. It is known that 20% of all CO2 consumed daily by plants returns to the atmosphere in the form of Volatile Organic Compounds (VOCs), which can strongly elicit plants/treatments. Because of this, testing possible eliciting molecules/stimuli without the use of physical barriers that can isolate the different treatments can bring great interferences to the results obtained and lead to misleading and biased conclusions. Given this fact, the present work sought to 1) evaluate the eliciting effects of a carrageenan-based biostimulant (Algomel PUSH®) to increase the quantitative and qualitative gains of wheat plants, 2) evaluate the effect of duration of plant elicitation carried out with the use of carrageenan, 3) quantify the existing interference in plant elicitation tests conducted in the form of a Randomized complete block design (RCBD) vs. Completely randomized design (CRD), with modifications and, 4) propose a methodology to be used for plant elicitation studies. The use of carrageenan showed a long-lasting effect on wheat plants. The fungicide used in the work negatively affected the primary and specialized metabolism of wheat plants. Elicitation in the open field, without the use of physical barriers to isolate the different treatments, caused an average interference of 22% in the plants that did not receive the elicitors.